Analisa Expected Monetary Value Produksi Kapal Ikan Fiberglass Menggunakan Metode Decision Tree - Romadhoni Romadhoni; Nurhasanah Nurhasanah (COSTING : Journal of Economic, Business and Accounting, 2020)
To make decisions in the production of fiberglass vessels in traditional shipyards in Bengkalis Regency, it is necessary to carry out economic calculations using the Expected Monetary Value (EMV) method related to the production of fiberglass ships and wooden ships using the decision tree method. This is done to determine the chances of the producers succeeding or not with the development of fiberglass ship products, then some forecasting will be conducted on various possibilities that will occur. These possibilities will be formulated with a decision tree model so that producers will be able to decide whether the fiberglass ship product can be continued or only continue by running the old product, which is producing wooden ships. The results of this modeling can later become a reference for producers to look for further solutions if it turns out that after modeling new product results, the fiberglass ship has a greater chance of failure compared to its chances of success. Based on the results of modeling using the decision tree model, it is expected that the opportunity for producers to succeed with their new products, namely fiberglass ships, will be obtained. Keywords: EMV, Fiberglass, Decision Tree, economic